2014
DOI: 10.1075/avt.31.07mor
|View full text |Cite
|
Sign up to set email alerts
|

Resultative constructions in heritage Ambon Malay in the Netherlands

Abstract: Domains where languages have two or more competing syntactic constructions expressing the same meaning may be problematic for bilingual heritage speakers. One such variable domain is the resultative constructions in heritage Ambon Malay, a variety spoken in the Netherlands by Dutch-Ambon Malay bilinguals. In Ambon Malay, resultatives are expressed mostly by means of verb serialization (SVC), although resultative prepositional phrases (PP) and adjectival phrases (AP) also occur. In Dutch, resultative constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Previous studies noticed that in Chinese as L2 learners' acquisition of pivotal sentences and serial-events sentences, they had the problems of underusage and misusages (e.g., [21], [27]). The second-generation heritage language learners were also found to under-employ serial-events sentences in previous studies (e.g., [4], [14], [15]). However, these studies investigated L2 learners from different L1s and regarded misuses as a developmental problem.…”
Section: Introductionmentioning
confidence: 56%
“…Previous studies noticed that in Chinese as L2 learners' acquisition of pivotal sentences and serial-events sentences, they had the problems of underusage and misusages (e.g., [21], [27]). The second-generation heritage language learners were also found to under-employ serial-events sentences in previous studies (e.g., [4], [14], [15]). However, these studies investigated L2 learners from different L1s and regarded misuses as a developmental problem.…”
Section: Introductionmentioning
confidence: 56%
“…'Two predicate' constructions such as those found in Ambon Malay are a typical feature of the Malay varieties that are spoken in eastern Indonesia. In these varieties, complex events tend to be expressed through two or more consecutive verbal predicates (referred to as 'serial verb constructions'10 in Paauw, 2008: 232-236; see also Moro, 2014). In our dataset there are nine instances where T is fronted, against one instance where R is fronted.…”
Section: Give-constructions In Ambon Malaymentioning
confidence: 99%
“…Ambon Malay prefers po always, while Dutch has a bias for do in corpus data, and for po in de-contextualised elicited data. It has been demonstrated (Boumans, 2006;Onar Valk and Backus, 2013;Moro, 2014) that heritage speakers tend to adapt the frequency of a construction in the heritage language to the frequency of the 'corresponding' construction in their dominant language. In this case, this means that the frequency of po and do constructions in heritage Ambon Malay will be adapted to the Dutch frequencies, and thus be different from that of homeland Ambon Malay.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Heritage speakers of Ambon Malay are bilingual in Dutch and Ambon Malay, but have Dutch as their dominant language. Previous studies (Aalberse & Moro, 2014;Huwaë, 1992;Lekawael, 2011;Moro, 2014;Moro & Klamer 2015;Tahitu, 1989) have shown that Ambon Malay in the Netherlands is undergoing a substantial number of changes owing to unbalanced bilingualism in general, and to the intense contact with Dutch in particular.…”
Section: Introductionmentioning
confidence: 99%